Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 2 - Equations, Inequalities, and Problem Solving - 2.2 Using the Principles Together - 2.2 Exercise Set - Page 95: 109



Work Step by Step

Using the order of operations and the properties of equality, the solution to the given equation, $ 2x(x+5)-3(x^2+2x-1)=9-5x-x^2 $, is \begin{array}{l} 2x^2+10x-3x^2-6x+5x+x^2=9-3 \\\\ (2x^2-3x^2+x^2)+(10x-6x+5x)=9-3 \\\\ 9x=6 \\\\ x=\dfrac{6}{9} \\\\ x=\dfrac{2}{3} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.